Territory, technosphere and psychosphere: foundations of digital sovereignty - Ribeiro, Luis Henrique Leandro; Tavares, Lucas Cortez (Geografares, 2026)
The article analyzes the digitalization of territory, current phase of the technical-scientific-informational milieu, emphasizing the disputes over the meanings of digital sovereignty in Brazil and the ongoing popular period of history. Based on the categories of technosphere and psychosphere, it argues that sovereignty involves the simultaneous control of technical infrastructures and of the meanings of actions that guide the use of territory as both resource and shelter. It discusses the role of big techs, datafication, and platformization in the production and organization of space and in the reproduction of technological dependency, characterized as data colonialism. The analysis of an emerging core of public policies aimed at digitalization reveals tensions between regulation, development, and subordination to international capital. Finally, the article highlights the emergence of popular digital sovereignty as an alternative, grounded in the collective appropriation of technologies and in the construction of public and community digital infrastructures guided by the social function of technology.
Keywords: territory in use; popular period of history; popular digital sovereignty